2010
DOI: 10.1176/appi.ps.61.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mental Health Services by Nursing Home Residents After Hurricanes

Abstract: Nursing home staff should be trained to deliver disaster-related mental health intervention and in procedures for making referrals for follow-up evaluation and formal intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…Another notable gap revealed by earlier research examining the effects of hurricanes on nursing homes and supported by the findings of this study is that during disasters mental health is not a priority area Brown et al 2010;Laditka et al 2009). Although it is common practice to provide psychological first aid in response to people exposed to a potentially traumatic stressor, assisted living facility residents who are not sheltering in a public shelter run the risk of going untreated.…”
Section: Discussionsupporting
confidence: 40%
“…Another notable gap revealed by earlier research examining the effects of hurricanes on nursing homes and supported by the findings of this study is that during disasters mental health is not a priority area Brown et al 2010;Laditka et al 2009). Although it is common practice to provide psychological first aid in response to people exposed to a potentially traumatic stressor, assisted living facility residents who are not sheltering in a public shelter run the risk of going untreated.…”
Section: Discussionsupporting
confidence: 40%
“…Consistent with the findings of these government investigations, a statewide survey of Florida NH directors of nursing and administrators also revealed a need for disaster mental health services for residents (Brown et al, 2008). Yet a review of facility disaster plans and NH regulations in 2006 showed that procedures for providing residents with disaster mental health interventions were not included as part of the recovery process.…”
Section: Introductionmentioning
confidence: 58%
“…In contrast to community-dwelling elders, nursing home (NH) residents are at greater risk for disaster-related adverse psychological outcomes (Brown, Rothman, & Norris, 2007; Dosa et al, in press; Laditka et al, 2008); yet during the recovery phase they are consistently underserved in regards to psychological intervention (Brown, Hyer, & Polivka-West, 2007; Brown, Hyer, Schinka, Frazier, & Mando, 2008; Centers for Medicare and Medicaid Services [CMS], 2006). Until the publication of several government reports that specifically noted that NH residents experienced adverse psychological consequences due to the 2005 hurricanes, the disaster mental health needs of this subgroup were generally not recognized (Administration On Aging, 2006; CMS, 2006; Department of Health and Human Services, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Brown et al 38 Douglas et al 39 Falk et al 8 Gifford et al 3 Menon et al 40 qualitative and quantitative portion of the study in phases, such that 1 approach builds upon the findings of the other approach. Among 30 selected articles, 9 studies used connection approach to mix their data.…”
Section: Connectionmentioning
confidence: 99%
“…3 Researchers conducted qualitative data collection after an intervention to explore underlying factors influencing nursing home residents' use of mental health services after hurricanes. 38 …”
Section: Embeddingmentioning
confidence: 99%